The Relationship Between Sufficient Knowledge and Behavior of Medical Students in Faculty of Medicine Universitas Sumatera Utara regarding Acne Vulgaris - Sitepu, Josapat Bima Sakti; Hazlianda, Cut Putri (SCRIPTA SCORE Scientific Medical Journal, 2025)
ABSTRACT Acne vulgaris is a chronic inflammation of pilosebaceous follicles caused by Propionibacterium acnes. The clinical symptoms are polymorphic skin eruption, especially blackheads, non-inflammatory papule, pustule, nodule, and cyst formation. Generally, patients tend to complain of the aesthetic disfigurement caused by acne vulgaris. Even though it is not life-threatening, acne vulgaris can seriously harm patientsâ€™ confidence and might cause depression. One of risk factors is lack of knowledge and bad behavior. This research aimed to study the knowledge and behavior of medical students in University of North Sumatra regarding acne vulgaris in 2018. The research was observational cross-sectional study. Eighty-eight medical students in University of North Sumatra that fulfilled the inclusion criteria in this study were recruited and were randomized using consecutive sampling. The data was obtained by filling in the questionnaire to evaluate their knowledge and behavior. The accumulated data were processed with computer. The level of knowledge of the medical students in University of North Sumatra is 43.2% (sufficient) and the behavior of the medical students in University of North Sumatra was 68.2% (sufficient). There was a significant relationship between knowledge and behavior of the medical students in University of North Sumatera and acne vulgaris. Keywords: Acne Vulgaris, Behavior, Knowledge, University Student Â  ABSTRAK Acne vulgaris merupakan inflamasi kronis folikel pilosebasea yang disebabkan oleh Propionibacterium acne. Gejala klinis yang muncul umumnya berupa erupsi kulit polimorfik dengan dominasi komedo hitam, papula non-inflamasi, pustula, nodus, dan kista. Secara umum, pasien sering mengeluhkan gangguan kosmetik yang ditimbulkan akibat acne vulgaris. Walaupun tidak mengancam jiwa, acne vulgaris dapat membahayakan pasien karena dapat menyebabkan krisis kepercayaan dan depresi. Salah satu faktor risiko adalah pengetahuan dan perilaku buruk. Penelitian ini bertujuan untuk menilai pengetahuan dan sikap mahasiswa kedokteran di Universitas Sumatera Utara (USU) tentang acne vulgaris pada 2018. Penelitian ini berupa penelitian observasional potong-lintang. Sampel penelitian adalah 88 mahasiswa kedokteran USU yang memenuhi kriteria inklusi yang kemudian diacak menggunakan metode consecutive sampling. Data berasal dari kuesioner yang maharsiswa dengan acne vulgaris untuk menilai pengetahuan dan sikap yang selanjutnya diolah menggunakan komputer. Pengetahuan sampel didapati 43,2% (cukup), sedangkan sikap 68,2% (cukup). Penelitian berkesimpulan terdapat hubungan signifikan antara pengetahuan dan sikap mahasiswa kedokteran USU terkait acne vulgaris. Kata Kunci: Acne vulgaris, mahasiswa kedokteran, pengetahuan, sikap